Historical Evolution and Contemporary Implementation of Islamic Justice in Egypt: From Classical Courts to Modern Legal Pluralism - Ihsan, Arif Jum'atul; Eva, Yusnita; Zulfan, Zulfan; Husaini, Jeffry; Jumadi, Fadli; Rahman, Doris Andika; Sulaiman, Hari Devidra (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
The Islamic judicial system in Egypt has historically served as a central institution for the administration of justice based on Islamic law, particularly in matters of family law, inheritance, and civil dispute resolution. Over time, this system has undergone significant transformation influenced by political change, colonial intervention, and legal modernization, which reshaped its institutional structure, authority, and relationship with the modern state. Despite extensive scholarship on Islamic law and legal reform in Egypt, studies that systematically examine the historical development and institutional transformation of Islamic justice within the contemporary national legal framework remain limited. This study aims to analyze the evolution of the Islamic judicial system in Egypt by exploring its historical foundations, institutional changes, and integration into the modern state legal system. Employing a qualitative approach with historical-analytical methods, this research examines classical Islamic legal texts, Egyptian legislation, and relevant scholarly literature. The findings indicate that Islamic justice in Egypt has experienced substantial transformation through legal codification and the establishment of national courts, while maintaining the substantive role of Sharia principles, particularly in personal status law. This study highlights the ongoing negotiation between Islamic legal tradition and modern legal governance in contemporary Egypt.